2021
DOI: 10.2147/cmar.s294718
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery Impact on the Systemic Inflammatory Response of Patients Following Gynecological Oncology Surgery: A Prospective Randomized Study

Abstract: Objective Enhanced recovery after surgery (ERAS) protocol has widely gained acceptance in gynecological surgery. Its safety and efficacy should be evaluated fully via well-designed, randomized, control trials. The main objective of our study is to compare the ERAS protocol with the conventional perioperative care program after gynecological oncology. Furthermore, the secondary objectives of our study are the identification of markers that allow us to evaluate the effectiveness of the application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…according to gynecological surgery guidelines, multimodal analgesia combined with eras protocols resulted in reduced opioid consumption, less postoperative nausea and vomiting (PONV) and earlier discharge times, reducing healthcare costs. [4][5][6][7][8][9] the aim of the present study was to compare the efficacy of intrathecal morphine (IM) injection as part of multimodal intravenous analgesia protocols with prophylaxis of postoperative nausea and vomiting versus intravenous patient-controlled analgesia (Pca) in women undergoing to two different gynecological surgical approaches: laparoscopic hysterectomy or laparotomic myomectomy. the dose-sparing effect of intravenous rescue analgesics, the intensity of postoperative pain, side effects and length of hospitalization were evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…according to gynecological surgery guidelines, multimodal analgesia combined with eras protocols resulted in reduced opioid consumption, less postoperative nausea and vomiting (PONV) and earlier discharge times, reducing healthcare costs. [4][5][6][7][8][9] the aim of the present study was to compare the efficacy of intrathecal morphine (IM) injection as part of multimodal intravenous analgesia protocols with prophylaxis of postoperative nausea and vomiting versus intravenous patient-controlled analgesia (Pca) in women undergoing to two different gynecological surgical approaches: laparoscopic hysterectomy or laparotomic myomectomy. the dose-sparing effect of intravenous rescue analgesics, the intensity of postoperative pain, side effects and length of hospitalization were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 surgical acute pain is a modifiable risk factor for the develop-ment of chronic postoperative pain and is a key component of enhanced recovery after surgery (eras) protocols. 3,4 Multimodal analgesia, i.e., the administration…”
mentioning
confidence: 99%
“…Such experimental results show that the systemic inflammatory response in the ERAS group was significantly inhibited by the perioperative ERAS protocol. In the study by Peng et al (8), the ERAS protocol was used in gynecological surgery. A total number of 130 surgical patients with gynecologic tumors were included in this study.…”
Section: Introductionmentioning
confidence: 99%
“…The Enhanced Recovery After Surgery (ERAS) pathway was designed to improve the recovery of surgical patients through the preoperative, operative, and postoperative stages [1]. This evidence-based protocol provides active strategies to minimize the stress of surgery, reduce postoperative complications, decrease hospital stay, and facilitate improved functional recovery [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Morbidity associated with surgery affects patient outcomes, quality of life, and survival rates [4]. Although most investigations of ERAS protocols are implemented in open surgery, patients who undergo laparoscopic surgery can also benefit from following the ERAS protocols, according to multiple studies [1]. Numerous reports have demonstrated that operative and post-operative complications can interfere with overall survival rate [4].…”
Section: Introductionmentioning
confidence: 99%